Movers and Stayers: How Residential Selection Contributes to the Association between Female Body Mass Index and Neighbourhood Characteristics - Smith, Ken R. (Int J Obes (Lond), 2016)
BACKGROUND/OBJECTIVES: To examine how a woman's current Body Mass Index (BMI) is associated with non-random residential migration that is based on the average BMI of her origin and destination neighbourhoods. SUBJECTS/METHODS: Among women having at least two children, all birth certificates from Salt Lake County from 1989-2010 (n=34,010) were used to obtain pre-pregnancy weights prior to the first and second births, residential location and socio-demographic information. Census data were used for measures of walkability of neighbourhoods. RESULTS: After adjustments for age, education, race/ethnicity, and marital status, obese women living in the leanest neighbourhoods are found to be three times more likely (OR= 3.03, 95% CI 2.06-4.47) to move to the heaviest neighbourhoods relative to women with healthy weight (BMI between 18-25). Conversely, obese women in the heaviest neighbourhoods are 60% less likely (OR=0.39, 95% CI: 0.22-0.69) to move to the leanest neighbourhoods relative to healthy weight women. Indicators of relatively greater walkability (older housing, greater proportion of residents who walk to work) and higher median family income characterize leaner neighbourhoods. CONCLUSIONS: The findings are consistent with the hypothesis that non-random selection into and out of neighbourhoods accounts for some of the association between BMI and neighbourhood characteristics.